2005
DOI: 10.1111/j.1600-0404.2004.00345.x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial nitric oxide synthase gene interactions and the risk of ischaemic stroke

Abstract: The eNOS G894T or eNOS 894TT genotypes in combination with the MTHFR 677TT or ACE D/D genotype increases the risk of ischaemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
1
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 13 publications
4
39
1
1
Order By: Relevance
“…Gardemann et al (21 ) showed that the TT genotype of the methylenetetrahydrofolate reductase C677T gene polymorphism is associated with extent of coronary atherosclerosis in patients at high risk for CAD. To date, the G894T polymorphism of the eNOS gene has been linked to increased risk of stroke, myocardial infarction, coronary atherosclerosis, and venous thrombosis (22)(23)(24)(25). Previous studies from Japan and the United Kingdom have already suggested a role for the G894T polymorphism in the development of coronary atherosclerosis, with the excess risk being confined to TT894 homozygosity (18,26,27 ), as in our study.…”
Section: Discussionsupporting
confidence: 64%
“…Gardemann et al (21 ) showed that the TT genotype of the methylenetetrahydrofolate reductase C677T gene polymorphism is associated with extent of coronary atherosclerosis in patients at high risk for CAD. To date, the G894T polymorphism of the eNOS gene has been linked to increased risk of stroke, myocardial infarction, coronary atherosclerosis, and venous thrombosis (22)(23)(24)(25). Previous studies from Japan and the United Kingdom have already suggested a role for the G894T polymorphism in the development of coronary atherosclerosis, with the excess risk being confined to TT894 homozygosity (18,26,27 ), as in our study.…”
Section: Discussionsupporting
confidence: 64%
“…The present results indicate that polymorphisms in GCH1 (rs841) are independently associated with an increased risk for IS. In contrast, we failed to detect significant independent association with the rest of SNPs even though they have been suggested to be associated with cardiovascular diseases such as hypertension, coronary heart disease or stroke [21][22][23] .…”
Section: Discussioncontrasting
confidence: 48%
“…Therefore, the dysregulation of eNOS can lead to atherosclerosis, ischemic stroke, and various other vessel diseases (14)(15)(16)(17)(18). Related to these pathogenic conditions, three representative polymorphisms of the eNOS gene have been identified: i) -786T>C within the 5'-flanking region (14); ii) 27-bp deletion(a)/insertion(b) within the intron 4 (collectively designated as '4a4b') (19); iii) 894G>T within the exon 7 (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%